2020
DOI: 10.3390/ijms21113954
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Activity of P4503A4 and UGT1A10 Induced by Acridinone Derivatives C-1305 and C-1311 in MCF-7 and HCT116 Cancer Cells: Consequences for the Drugs’ Cytotoxicity, Metabolism and Cellular Response

Abstract: Activity modulation of drug metabolism enzymes can change the biotransformation of chemotherapeutics and cellular responses induced by them. As a result, drug-drug interactions can be modified. Acridinone derivatives, represented here by C-1305 and C-1311, are potent anticancer drugs. Previous studies in non-cellular systems showed that they are mechanism-based inhibitors of cytochrome P4503A4 and undergo glucuronidation via UDP-glucuronosyltranspherase 1A10 isoenzyme (UGT1A10). Therefore, we investigated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Studies have shown that C-1311 is a DNA intercalator and topoisomerase II inhibitor [ 54 ]. It caused the accumulation of cells in the G2/M phase and subsequent induction of apoptosis, necrosis, autophagy, mitotic catastrophe or accelerated senescence, wherein apoptosis was not the main cause of cell death in solid cancer cell lines, especially HCT116 [ 55 ] and H460 cells [ 56 ]. Therefore, it should be emphasized that the presented studies showed that UAs exhibit an entirely different cellular mechanism of action to C-1311.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that C-1311 is a DNA intercalator and topoisomerase II inhibitor [ 54 ]. It caused the accumulation of cells in the G2/M phase and subsequent induction of apoptosis, necrosis, autophagy, mitotic catastrophe or accelerated senescence, wherein apoptosis was not the main cause of cell death in solid cancer cell lines, especially HCT116 [ 55 ] and H460 cells [ 56 ]. Therefore, it should be emphasized that the presented studies showed that UAs exhibit an entirely different cellular mechanism of action to C-1311.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Interestingly, although both C-1305 and C-1311 undergo metabolic transformation to the glucuronidated forms upon overexpression of UGT1A10, UGT1A10 overexpression significantly increased the cytotoxicity of C-1305 but not C-1311. 28,29 These findings contribute to the understanding of the mechanisms of action of both compounds and encourage further studies on the C-1305 mode of action.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Some authors suggest that extrahepatic UGT1A10 also plays an important role in the metabolism and bioactivation of C-1305, and this biotransformation leads to enhanced proapoptotic activity of these glucuronide products. 28,29 Interestingly, although both C-1305 and C-1311 undergo metabolic transformation to the glucuronidated forms upon overexpression of UGT1A10, UGT1A10 overexpression significantly increased the cytotoxicity of C-1305 but not C-1311. 28,29 These findings contribute to the understanding of the mechanisms of action of both compounds and encourage further studies on the C-1305 mode of action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another aspect of the results described above is illustrated by Figure 9 , Figure 10 and Figure 11 . HPLC analysis indicated that HT-29 tumor cells, which are characterized by the highest levels of metabolic enzymes [ 79 ], are also the most susceptible to drug accumulation. This relates to all three studied compounds, but particularly to those possessing the additional methyl group in the acridine ring, C-2045 and C-2053.…”
Section: Discussionmentioning
confidence: 99%